Highway to Success in India : The Impact of the Golden Quadrilateral Project for the Location and Performance of Manufacturing - Ghani, Ejaz (World Bank, Washington, DC, 2013)
The infrastructure gap is one of the most significant impediments to India realizing its growth and poverty reduction potential. Although India s transport network is one of the most extensive in the world, accessibility and connectivity are limited. Only 20 percent of the national highway network (which carries 40 percent of traffic) is four-lane and one-fourth of the rural population does not have access to an all-weather road. It is estimated that the transport sector alone will require an investment of nearly US$500 billion over the next 10 years. This paper investigates the impact of the Golden Quadrilateral highway project on the Indian organized manufacturing sector using enterprise data. The Golden Quadrilateral project upgraded the quality and width of 5,846 km of roads in India. The analysis uses a difference-in-difference estimation strategy to compare non-nodal districts based on their distance from the highway system. It finds several positive effects for non-nodal districts located 0-10 km from the Golden Quadrilateral that are not present in districts 10-50 km away, most notably higher entry rates and increases in plant productivity. These results are not present for districts located on another major highway system, the North-South East-West corridor. Improvements for portions of the North-South East-West corridor system were planned to occur at the same time as the Golden Quadrilateral but were subsequently delayed. Additional tests show that the Golden Quadrilateral project s effect operates in part through a stronger sorting of land-intensive industries from nodal districts to non-nodal districts located on the Golden Quadrilateral network. The Golden Quadrilateral upgrades further helped spread economic activity to moderate-density districts and intermediate size cities.